Selecting on-demand delivery apps: a case study from Thailand. (22nd May 2020) - Syukur, Muhammad; Kosumsuriya, Anchisa; Jongsureyapart, Chatrudee
This paper aims to prioritise factors affecting customers' decision making in selecting a particular mobile app for delivery services. It employs the analytic hierarchy process (AHP) with four selected factors: payment method (PM), functionality (FT), added value (AV), and firms' characteristics (FC) while the brand alternatives are line man, grab bike, and send ranger. The sample for this research is a total of 18 experienced customers who reside in Bangkok metropolitan city. It is found that added value is the strongest factor that affects customers' selection on mobile apps, followed by functionality, firms' characteristics, and payment method. The most preferred on-demand delivery app is send ranger.